2020
DOI: 10.25259/jcis_173_2019
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcomes with Single-antenna High-powered Percutaneous Microwave Ablation for Primary and Secondary Hepatic Malignancies: Safety, Effectiveness, and Predictors of Ablative Failure

Abstract: Objective: Microwave ablation (MWA) of liver malignancies has gained much traction over the past 5 years. However, MWA carries relatively higher rates of residual disease compared to resection. Likelihood of MWA success is multifactorial and newer devices with more reliable ablation zones are being developed to overcome these drawbacks. This manuscript is a review of our first 100 liver ablations with the newer single antenna high powered MWA system. Materials and Methods: Retrospective chart review of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Several studies have compared the efficacy of first-generation MWA to that of RFA, which revealed that MWA had comparable safety and long-term efficacy for liver tumors with a diameter of <4 cm [ 18 , 19 , 26 ]. New MWA technologies have also been developed and attracted significant interest regarding their safety and efficacy, although there are few reports regarding new MWA technologies as appropriate treatment strategies [ 20 , 21 , 22 , 27 ]. To the best of our knowledge, this is the first study to evaluate the short-term and medium-term survival, efficacy and safety of MWA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have compared the efficacy of first-generation MWA to that of RFA, which revealed that MWA had comparable safety and long-term efficacy for liver tumors with a diameter of <4 cm [ 18 , 19 , 26 ]. New MWA technologies have also been developed and attracted significant interest regarding their safety and efficacy, although there are few reports regarding new MWA technologies as appropriate treatment strategies [ 20 , 21 , 22 , 27 ]. To the best of our knowledge, this is the first study to evaluate the short-term and medium-term survival, efficacy and safety of MWA.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the smaller number of antenna insertions makes MWA an attractive locoregional treatment for HCC. Moreover, the ablation area of MWA can be precisely controlled based on time and output power [ 21 , 22 ], which permits a single MWA antenna to treat small nodules (<1 cm) and larger nodules up to a size of 4 cm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial MWA systems were constrained by poor antenna design and the inability to achieve spherical ablation zones, causing significant damage to adjacent healthy tissues [ 45 , 46 ]. The major limitation of earlier MWA devices is the lack of predictability of the ablation zone size and shape, since it depends on the inherent characteristics of the target tissues.…”
Section: Introductionmentioning
confidence: 99%